Cat and Housefly: Unhuman Umwelten and Punitive Fantastika in M. John Harrison's Fiction. Issue 2 (1st July 2022) - Murphy, Timothy S.
Abstract : M. John Harrison's major fictional sequences Viriconium (1971–1985) and the Empty Space trilogy (2002–2012) refuse the quasi-theological world-building ambitions of conventional fantasy and sf, offering instead the paradoxical pleasures of imaginary worlds that fail to cohere and narrative mysteries that avoid resolution or closure. Harrison uses the biophilosophical concept of Umwelt, referring to a world of perception and action specific to a particular lifeform and inaccessible to other forms, as a conceptual alternative to the monolithic, reductive, and escapist logic shared by cult-fictions like The Lord of the Rings and fantastic crank-cults such as Scientology.